Audit Sistem Informasi Absensi Menggunakan Cobit 5 (Studi Kasus ; PT. PLN Persero Binjai) - Debby Ade prastiwi; Desiska Natalia Br purba; Farida hanum; Nurul qadarsih (International Forum of Researchers and Lecturers, 2024)
The development of information systems is now widely used in the business world, both in the living environment and even in the work environment, such as the use of the attendance information system at PT PLN PERSERO. Attendance in an agency is an important factor in human resource management. Accurate and objective information regarding an employee's attendance can present the quality and productivity of performance, determine the size of performance allowances and the general level of employee discipline in the agency. The process of recording and reporting employee absences is a repetitive process that is used at certain times such as entry time, departure time and holidays. It is recommended that audits of this system be carried out periodically or annually, so that the expected level of maturity can be achieved, and as a whole, not just the attendance information system, so that all aspects of work operations can also be evaluated so as to improve employee performance in general. From the results of the maturity level assessment, several findings were obtained in each domain studied, namely with the EDM03 domain having a value of 3.00, it was found that information and data security problems needed to be improved, with the EMD05 domain having a value of 2.93, problems were found that there were no written regulations that could be used as a reference, with domain AP015 with a value of 3.13 found a problem that there was still a difference between cost allocation and actual costs with domain 1P012 with a value of 3.07, a problem was found that there were no risk response regulations available, with domain DSS02 with a value of 3.13 there were no written regulations that could be used as a reference.